Multifunctional Photonics Nanoparticles for Crossing the Blood–Brain Barrier and Effecting Optically Trackable Brain Theranostics. (5th September 2016) - Singh, Ajay; Kim, Woong; Kim, Youngsun; Jeong, Keunsoo; Kang, Chi Soo; Kim, YoungSoo; Koh, Joonseok; Mahajan, Supriya D.; Prasad, Paras N.; Kim, Sehoon
Abstract : Theranostic photonic nanoparticles (TPNs) that cross the blood–brain barrier (BBB) and efficiently deliver a therapeutic agent to treat brain diseases, simultaneously providing optical tracking of drug delivery and release, are introduced. These TPNs are constructed by physical encapsulation of visible and/or near‐infrared photonic molecules, in an ultrasmall micellar structure (<15 nm). Phytochemical curcumin is employed as a therapeutic as well as visible‐emitting photonic component. In vitro BBB model studies and animal imaging, as well as ex vivo examination, reveal that these TPNs are capable of transmigration across the BBB and subsequent accumulation near the orthotopic xenograft of glioblastoma multiforme (GBM) that is the most common and aggressive brain tumor whose vasculature retains permeability‐resistant properties. The intracranial delivery and release of curcumin can be visualized by imaging fluorescence produced by energy transfer from curcumin as the donor to the near‐infrared emitting dye, coloaded in TPN, where curcumin induced apoptosis of glioma cells. At an extremely low dose of TPN, a significant therapeutic outcome against GBM is demonstrated noninvasively by bioluminescence monitoring of time‐lapse proliferation of luciferase‐expressing U‐87 MG human GBM in the brain. This approach of TPN can be generally applied to a broad range of brain diseases. Abstract : Brain theranostic nanoparticles that are capable of crossing the blood–brain barrier are developed. These micellar nanoparticles, assembled with photonic molecules and/or therapeutic phytochemicals, and whose fate is traceable by optical imaging, demonstrate efficient intracranial drug delivery and effective therapeutic outcomes against brain tumors.